A model for predicting load-displacement hysteretic behavior of PVC-CFRP confined concrete column-ring beam interior joints under low cyclic loading. (1st June 2021) - Song, Zekang; Yu, Feng; Zhang, Nannan; Fang, Yuan
Abstract: To investigate the seismic behaviors of the column-beam connection, ten PVC-CFRP confined concrete column-ring beam interior joints (PCCC-RBIJs) and one PVC confined concrete column-ring beam interior joint (control interior joint) are designed and five experimental parameters including the CFRP strips spacing, the ring beam reinforcement ratio, the frame beam reinforcement ratio, the ring beam width and the axial compression ratio are considered. Test results show that the PCCC-RBIJs are damaged by shear deformation while the CFRP strips and PVC tubes are not broken. The hysteretic curves of the PCCC-RBIJs are relatively full, indicating that the specimens have high energy dissipation capacity. The peak load and displacement of the PCCC-RBIJs increase as the ring beam reinforcement ratio, the frame beam reinforcement ratio, the ring beam width or the axial compression ratio increases. The descendent segment gradient of the skeleton curves declines with the increase of the ring beam width or the ring beam reinforcement ratio while it enhances with the increase of the frame beam reinforcement ratio or the axial compression ratio. On the basis of experimental research, a simplified skeleton curve calculation formula is proposed by determining the characteristic points of the skeleton curves, and the hysteretic rule of the PCCC-RBIJs is revealed based on the degenerated three fold line load–displacement ( P - Δ ) hysteretic model. Subsequently, a model for predicting the P - Δ hysteretic behavior of the PCCC-RBIJs is proposed.